The Role of the 2015 Agreement in Mobilising Climate Finance - Kato, Takayoshi (OECD/IEA Climate Change Expert Group Papers, 2014)
Shifting public and private investment from "brown" to "green" is an essential part of climate change. The post-2020 climate agreement to be agreed at COP 21 in December 2015 has the potential to play a significant role in signalling the importance of such a shift. This paper explores how the 2015 agreement could spur further mobilisation of climate finance by examining the current state of play regarding existing financing environments and mechanisms. These include examining the existing international institutional arrangements under the UNFCCC to see how balanced financing, co-ordination, streamlining and complementarity between institutions could be achieved. The paper also highlights the key role that in-country enabling environments can play in further mobilising public and private climate finance, and discusses how the 2015 agreement could enhance both "pull" and "push" factors for mobilisation. In addition, the paper also discusses how the agreement could facilitate the broad use of a spectrum of financial instruments and the further development of an enhanced system for measurement, reporting and verification of climate finance